Plate kinematics of the Rocas Verdes Basin and Patagonian orocline - Eagles, Graeme (Gondwana Research, 2016)
The processes of orocline formation are a topic of debate in geosciences. The Patagonian orocline has been a case in point for over a century. Large anomalous paleomagnetic pole rotations show that the orocline started to form at the same time as mid-Cretaceous closure of the Rocas Verdes Basin, today known from ophiolitic and basin fill remnants in the Patagonian and Fuegian Andes. Some studies therefore present bending of the Andes and closure of the basin as shared consequences of rotation of a small plate that was driven by subduction-related forces at the Pacific margin of Gondwana. An alternative view of the orocline is as a product of Cretaceous to Paleogene-aged sinistral oblique convergence at the plate-boundary scale. Geological data from Tierra del Fuego have been interpreted in support of both views. Here, I test these suggestions by comparing the Rocas Verdes Basin's tectonostratigraphy to predictions of a plate kinematic model for fragmentation of the western interior of Gondwana. The model is sufficient to explain the known history of basin opening to a width of ~ 100–300 km during the period 152–141 Ma and later closure in oblique plate convergence. As this convergence occurred by motion around a distant Euler pole, it could not have produced the Patagonian orocline by rotation of a lithospheric plate on its Pacific flank. The large anomalous paleomagnetic rotations of Tierra del Fuego, instead, are likely to have occurred within the crust by rotation and deformation of regional strike-slip faults and the intervening rocks to accommodate oblique convergence of the South American and Antarctic plates between Albian and Paleocene times.